The effects of flip angle optimization on the precision and reproducibility of feature tracking derived strain assessment in contrast enhanced bSSFP cine images. Issue 102 (May 2018) - Kuetting, Daniel L.R.; Feisst, Andreas; Dabir, Darius; Luetkens, Julian; Homsi, Rami; Thomas, Daniel; Schild, Hans H.; Sprinkart, Alois M.
Abstract: Objectives: The aim of this study was to investigate whether a flip angle adaptation, which is known to improve SNR and CNR in post contrast SSFP imaging, improves the precision and reproducibility of Feature Tracking (FT) derived strain assessments in post contrast bSSFP imaging. Methods and results: At 1.5T balanced SSFP midventricular short axis cine images were acquired with various flip angles (FA) before (FA = 50°) and 5 min after (FAs = 50°, 80°, 90°, 100°) injection of double dose Gadobutrol. FT derived systolic circumferential strain was then calculated for all pre- and post-contrast images, the intra- and inter-observer variability of strain measurements was assessed. FT derived midventricular peak systolic circumferential strain (PSCS) derived from unadapted (FA: 50°) contrast enhanced bSSFP images was significantly lower than strain derived from unenhanced bSSFP images (−16.45 ± 5.1% vs −20.57 ± 6.2%; p < 0.001) and showed low agreement (mean difference of −4.13 ± 2.4, 95% CI:−5.3 to −3 ) in all 20 subjects. After adaption of the flip angle (FA: 100°), agreement between strain derived from unenhanced and adapted contrast enhanced bSSFP images (−20.57 ± 6%) was strong ( 0.01 ± 0.9, CI:−0.43 to 0.41). In comparison to intra- and interobserver variability of strain derived from unenhanced images (intra 2.9%; inter: 3.9%), strain measurements derived from adapted contrast enhanced images (FA: 100°) showed a slightly lower variability (intra: 2.5%; inter: 2.3%). Conclusion: If flip angle adaptation is performed, FT based strain analysis may be performed on contrast enhanced bSSFP cine images without loss of precision and accuracy.